2007
DOI: 10.1080/03601270601161181
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering Among Older Spanish Adults: Does the Type of Organization Matter?

Abstract: This study in Spain explored three aspects of older adult volunteering (motivations, satisfaction, and perceptions of benefits and drawbacks) and examines to what extent these aspects are influenced by the type of organization and other factors (sociodemographic variables and level of volunteering). The sample consisted of 88 older adults volunteering in 3 different organizations: management, cultural actions, and social care. Participants completed a self-administered questionnaire. Results show that voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
1
10
0
3
Order By: Relevance
“…For the third type of analysis, Windsor et al (2008) categorized their participants' volunteering into 11 differ ent types (e.g., fundraising, teaching, coaching, preparing food) but found that only one type differentially related to psychosocial outcome: Volunteering in management or committee roles was related to greater positive affect, but only for women. In contrast to that finding were the results from the descriptive study by Celdran and Villar (2007), who found that volunteering was asso ciated with an increased sense of self-esteem and mastery, but only for those volunteering in social services or cultural organizations, not in management organizations. Some investigators have re ported greater beneficial effects for those seniors volunteering for religious than nonreligious causes (McIntosh & Danigelis, 1995;Musick & Wilson, 2003;Oman et al, 1999), but these results were not replicated by Morrow-Howell et al (2003).…”
Section: Supposition 1: Volunteering Increases Social Physical and mentioning
confidence: 66%
See 1 more Smart Citation
“…For the third type of analysis, Windsor et al (2008) categorized their participants' volunteering into 11 differ ent types (e.g., fundraising, teaching, coaching, preparing food) but found that only one type differentially related to psychosocial outcome: Volunteering in management or committee roles was related to greater positive affect, but only for women. In contrast to that finding were the results from the descriptive study by Celdran and Villar (2007), who found that volunteering was asso ciated with an increased sense of self-esteem and mastery, but only for those volunteering in social services or cultural organizations, not in management organizations. Some investigators have re ported greater beneficial effects for those seniors volunteering for religious than nonreligious causes (McIntosh & Danigelis, 1995;Musick & Wilson, 2003;Oman et al, 1999), but these results were not replicated by Morrow-Howell et al (2003).…”
Section: Supposition 1: Volunteering Increases Social Physical and mentioning
confidence: 66%
“…Importantly, this review focuses on the benefits associated with volunteering and not its potential costs. For dis cussion of the costs (and benefits) of volunteering for both volun teers and organizations, we refer readers to Handy andMook (2011) andCeldran andVillar (2007).…”
Section: Focus On the Benefits Associated With Volunteeringmentioning
confidence: 99%
“…Further, the review by Anderson et al (2014) of 73 studies showed volunteerism in older adults is associated with reduced depression, better health, improved cognitive activity, improved psychosocial performance (e.g., self-esteem, life satisfaction), and fewer functional limitations. Yet, Celdran and Villar (2007) found that the satisfaction older adults have with volunteering and the setbacks they encounter when volunteering depend on the type of volunteer activity, with higher benefi ts and fewer drawbacks occurring when volunteering involves assisting vulnerable others. Given the benefi ts reported for volunteerism and for continuing education, service learning is an attractive opportunity to tie volunteerism and education together for older students, yet little is known about their combined impact on the student.…”
Section: Student Benefi Ts From Service Learning In Continuing Educationmentioning
confidence: 99%
“…Again, while less is known about the influence of individual or organisational characteristics on the barriers to continued involvement, there are some studies that explore this dimension. Celdrán and Villar (2007), for example, showed that the type of organisation and some socio-demographic characteristics, such as volunteers' age and income, had a significant influence on older volunteers' perceptions of drawbacks associated with participation. A study by Tang, Morrow-Howell and Choi (2010) found that income, health and some characteristics of the volunteer programme, such as the activity type or the duration of the involvement, were significant in predicting volunteers' turnover.…”
Section: Introductionmentioning
confidence: 99%